Conversion of the Spanish WordNet databases into a Prolog-readable format. - Julián-Iranzo, Pascual; Rigau, Germán; Sáenz-Pérez, Fernando; Velasco-Crespo, Pablo (Language Resources & Evaluation, 2025)
WordNet is a lexical database for English that is supplied in a variety of formats, including one compatible with the Prolog programming language. Given the success and usefulness of WordNet, wordnets of other languages have been developed, including Spanish. The Spanish WordNet, like others, does not provide a version compatible with Prolog. This work aims to fill this gap by translating the Multilingual Central Repository (MCR) version of the Spanish WordNet into a Prolog -compatible format. Thanks to this translation, a set of Spanish lexical databases are obtained, which allows access to WordNet information using declarative techniques and the deductive capabilities of the Prolog language. Also, this work facilitates the development of other programs to analyze the obtained information. Remarkably, we have adapted the technique of differential testing, used in software testing, to verify the correctness of this conversion. In addition, to ensure the consistency of the generated Prolog databases, as well as the databases from which we started, a complete series of integrity constraint tests have been carried out. In this way we have discovered some inconsistency problems in the MCR databases that have a reflection in the generated Prolog databases and have been reported to the owners of those databases.